The effect of photographic activity schedules on moderate‐to‐vigorous physical activity in children with autism spectrum disorder. Issue 2 (8th November 2020) - Becerra, Lorraine A.; Higbee, Thomas S.; Vieira, Mariana C.; Pellegrino, Azure J.; Hobson, Katelin
Abstract : Regular moderate‐to‐vigorous physical activity (MVPA) has been linked to improved bone health, muscular fitness, cognitive function, sleep, and a reduced risk of depression and obesity. Many children are not engaging in the recommended amount of physical activity. Furthermore, children with autism spectrum disorder (ASD) were found to engage in less physical activity than their peers of typical development. We extended previous research by conducting a physical activity context assessment, which included a comparison of indoor to outdoor activities to evaluate which environment produced the lowest percent of MVPA as recorded by the Observational System for Recording Physical Activity in Children . Given the utility of activity schedules to increase self‐management and independent engagement during unstructured and low‐preferred tasks, we then taught 3 preschool children diagnosed with ASD to use photographic activity schedules to increase the number of different activities that met the definition of MVPA in the 2 lowest‐responding conditions of the physical activity context assessment. MVPA remained low during baseline sessions for all participants and immediately increased with the introduction of activity schedule teaching. All participants quickly met activity schedule teaching mastery criterion and demonstrated high levels of MVPA in generalization and maintenance probes without additional teaching.